2009
DOI: 10.1139/z09-097
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for developmental plasticity of color patterns in response to rearing substrate in pygmy grasshoppers

Abstract: Abstract:Color polymorphisms in animals may result from genetic polymorphisms, developmental plasticity, or a combination where some phenotypic components are under strong genetic control and other aspects are influenced by developmental plasticity. Understanding how color polymorphisms evolve demands knowledge of how genetic and epigenetic environmental cues influence the development and phenotypic expression of organisms. Pygmy grasshoppers (Orthoptera, Tetrigidae) vary in color pattern within and among popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…2). My overall results thus support the notion that pygmy grasshopper color morphs are strongly influenced by genetic cues or epigenetic maternal effects, but little affected by post-hatching developmental plasticity in response to environmental cues (Nabours 1929;Forsman et al 2002;Ahnesjö and Forsman 2003;Karlsson et al 2008;Karlsson et al 2009;Karlsson and Forsman 2010) (but see Hochkirch et al 2008). …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…2). My overall results thus support the notion that pygmy grasshopper color morphs are strongly influenced by genetic cues or epigenetic maternal effects, but little affected by post-hatching developmental plasticity in response to environmental cues (Nabours 1929;Forsman et al 2002;Ahnesjö and Forsman 2003;Karlsson et al 2008;Karlsson et al 2009;Karlsson and Forsman 2010) (but see Hochkirch et al 2008). …”
Section: Discussionsupporting
confidence: 71%
“…Some morphs are monochrome but others have distinct pattern elements, such as longitudinal stripes along the median pronotum or specks or spots on the pronotum or jumping legs. All individuals are yellowish at hatching but they attain a darker brownish color within about 1 h. The different color morphs are indistinguishable in the first instars and their colors and patterns become more easily detectable, and alternative color morphs can be more accurately classified, as individuals grow larger (Karlsson et al 2009). …”
Section: Study Speciesmentioning
confidence: 96%
See 1 more Smart Citation
“…Ground colours are black, brown, reddish-brown, olive green, and light grey, and some morphs are monochrome while others have distinct specks, spots or a longitudinal stripe on the dorsal surface of the pronotum (Karlsson et al 2008;Caesar et al 2010). Data from an extensive breeding program on closely related Tetrigid species have shown that colour morphs are genetic (Nabours 1929), and more recent investigations of T. subulata have uncovered strong family effects, a high resemblance of colour patterns between mothers and offspring, and no developmental plasticity of colour pattern in response to environmental cues (Karlsson et al 2009;Karlsson and Forsman 2010;Forsman et al 2011) (but see Hochkirch et al 2008). Previous studies have also uncovered morphological, behavioural (Forsman 2000;Ahnesjö and Forsman 2006), physiological (Forsman 1997) and life-history (Forsman 1999a;Forsman et al 2002) differences among morphs.…”
Section: Study Species and Experimental Animalsmentioning
confidence: 99%
“…The genetic mechanisms underpinning the variation in color and pattern, and associated traits, in pygmy grasshoppers are not known in any detail. However, results from captive breeding, parent offspring resemblance studies, common garden and split-brood design-rearing experiments indicate that color morphs are genetically determined and not influenced by developmental plasticity (e.g., Karlsson et al 2009. Pygmy grasshopper color morphs represent integrated phenotypes that covary with other ecologically important traits such as preferred body temperatures, thermal physiology, reproductive life history (egg and clutch size, inter-clutch interval), body size, predator avoidance behavior, microhabitat utilization, and diet (e.g., Caesar et al 2010, and references therein).…”
Section: Introductionmentioning
confidence: 99%